Macs of Traction (International Journal of Engineering and Computer Science, 2015)
Traction is a physical process in which a tangential force is transmitted across an interface between two bodies through dry friction or an intervening fluid film resulting in motion, stoppage or the transmission of power. Traction system is classified into electric and non-electric. Electric traction satisfies most of the requirements of an ideal traction system which are not met by the use of non-electric traction. Electric traction consists of both AC and DC supply systems. Generally traction motors used are Dc series motors.Railways are the world's second-largest railway. Safe transportation of passengers is the key business objective of any transportation system. Railways are recognized as the safest mode of mass transportation and Safety has been recognized as the key issue for the railways and one of its special attributes. ACD is ‘self-acting’ microprocessor-based data communication equipment patented by KRCL that works ‘round-the-clock’. Different variants of ACDs when installed on Locomotives (along with their Auto-Braking Units), Guard Vans/SLRs, Stations and at Level Crossings (both manned as well as un-manned), form an ‘ACD Network’.